Biological Traits Of Fungal Pathogens Affecting Bulb Flowers And Methods Of Control. - Surayyo Misirova (Genius Journals, 2024)
The experiments were carried out in floriculture farms located in Namangan region during 2017-2019 years, and laboratory work was carried out at floriculture centers in Namangan region of the Republic of Uzbekistan. 19 species and 5 forms of fungal pathogens were detected in 7 species of bulb flowers grown in the Namangan regions of the Republic of Uzbekistan
Keywords: pathogens; grown; floriculture; Uzbekistan